Duloxetine Contributing to a Successful Multimodal Treatment Program for Peripheral Femoral Neuropathy and Comorbid ‘Reactive Depression’ in an Adolescent - Ludmyla Kachko; Shiri Ben Ami; Alon Liberman; Einat Birk; Sefi Kronenberg (Pain Research and Management)
In the United States, duloxetine has been approved for the treatment of major depressive disorder, diabetic peripheral neuropathic pain and fibromyalgia in the adult population. Data regarding the use of duloxetine in the pediatric population, however, are very limited. Femoral nerve injury is a rare complication of cardiac catheterization. In the case described, duloxetine contributed to a successful multimodal treatment program for peripheral neuropathic pain due to femoral neuropathy in an adolescent with ‘reactive depression’ and conversion symptoms. To the best of the authors’ knowledge, the present article is only the third such report on this dual use of duloxetine in children and adolescents, and the first report of such treatment following femoral neuropathy induced by cardiac catheterization.